The hybrid rhetorical ethos - Mateus, Samuel (2021)
There are three main schools for the study of the ethos: the pragmatic-discursive; the symbolic interactionist, and the rhetorical one. This paper aims to give an encompassing and fuller perspective on the rhetorical ethos that can be useful to the contemporary uses of the persuasive communication, including media communication such as advertising or marketing communication. Primarily, it outlines the conceptual employments ethos has suffered by through different subjects. Subsequently, it briefly enumerates the major rhetorical traditions; lastly, it postulates the rhetoric ethos as a hybrid notion that includes both a projected and an intended dimension. We hope this distinction allows us to better will envisage the persuasive communication further than the forum/agora and its several digital uses in the 21th century.